Fungsi Pendidikan Kewarganegaraan Sebagai Pertahanan Nasional - Rindi Rendiyawati; Dinie Anggraeni Dewi (Departement of Mathematics Education, 2021)
This study aims to provide an overview of how to maintain national defense among young people, knowing that now many young people do not care about the rules. The research method uses a quantitative approach with a case study method. Research informants are doing a google form questionnaire where students fill out a questionnaire that is already available and the researcher presents the results of the google form. This success from the point of view of Citizenship Education (PKN) is the development of civic virtue which is the estuary of the PKN learning objectives. Citizen virtue in the form of defending national defense among students.